Determinants of Poor Diet Quality among Elderly with Low Socioeconomic Status - Nazri, Nurul Syahidah; Vanoh, Divya; Leng, Soo Kah (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
The purpose of this study was to evaluate the factors that contribute to the elderly with low socioeconomic status eating poor-quality diets. Two hundreds and ninety three (293) senior citizens, including 136 men and 157 women, were sought out from five districts in Kelantan. Data on socio-demography, medical history, empty nest, depressive symptoms and diet history were obtained through an interview-administered method. Anthropometry measurement including height, weight and circumferences (waist, hip, calf and mid-upper arm) were measured. Body composition were measured using body composition monitor to obtain muscle mass and fat mass. Blood pressure were measured using blood pressure monitor. The Asian Working Group for Sarcopenia (AWGS) algorithm was used to determine the diagnosis of sarcopenia. 48.8% of the participants were underweight. The majority of participants fell short of the suggested daily calorie consumption. 42% of the participants had poor diet quality according to Healthy Eating Index (HEI) score. Hypercholesterolemia and poor Short Physical Performance Battery (SPPB) score were found to be risk factors of poor diet quality. Therefore, nutrition interventions are important to help low-income families especially with older adults to improve their nutritional status for reducing risk of sarcopenia and chronic diseases.